Parenting Style in Early Marriage Mothers in Indonesia - Irwanto, Irwanto; Ikhtiar, Ilham; Adi, Annis Catur; Putri, Andini Octaviana (Indonesian Journal of Medicine, 2019)
Background: Mothers who were married too young have a higher risk of to experience psychological and emotional problems influencing parenting style, which may have an impact on child development. However, prevalence of parenting style in early marriage mothers in Indonesia is still unknown. This study aimed to determine the prevalence of adopted parenting style on early marriage mothers.Subjects and Method: A cross-sectional study was conducted in Martapura, Banjar Regency, South Kalimantan, Indonesia, from April 1 to May 30, 2018. Mothers who were married in early age (<21 years old) were enrolled using simple random sampling. The dependent variable was parenting style. The independent variables were education, family income, and number of children. Parenting style was measured by short version of parenting style and dimension questionnaire (PSDQ). The data were analyzed by Spearman test.Result: Authoritative parenting style is the most common parenting style (54.6%), followed by authoritarian (32.7%), and permissive (12.7%) parenting style. Education level (r= -0.07; p= 0.325) decreased parental parenting style, but it was statistically non-significant. Family income (r= 0.72; p= 0.302) and number of children (r= 0.27; p= 0.700) increased parental parenting style, but it was statistically non-significant.Conclusions: Education level decreases parental parenting style, but it is statistically non-significant. Family income and number of children increase parental parenting style, but it was statistically non-significant.Keywords: parenting style, early marriageCorrespondence: Irwanto. Department of Child Health, Faculty of Medicine, Universitas Airlangga. Jl. Prof. Dr. Moestopo 6-8, Surabaya, East Java, Indonesia. Email: Irwanto.idris@gmail.com. Mobile +62816500818.Indonesian Journal of Medicine (2019), 4(4): 313-320https://doi.org/10.26911/theijmed.2019.04.04.03